On international economic integration in the light of sustainable development - N. P. Kharchenko (Вестник Северо-Кавказского федерального университета)
The article presents the problem of sustainable development of international business strategies. Due to the weakening of many barriers to international trade in the second half of the 20th century, firms began to implement global strategies in order to gain a competitive advantage. Today, some industries benefit more from the process of globalization than others, just as some countries have a comparative advantage over others in certain areas. To create a successful global sustainability strategy, leaders need to understand the nature of global industries and the dynamics of global competition. The article defines the concept of sustainable development of international strategy and groups the reasons for companies to enter the international level with the greatest performance, proves the obligation of firms to standardize their own products or alternative transfer to a foreign market by the example of joint ventures and international alliances.